1991
DOI: 10.1007/bf00164701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrition of Monascus sp. on formation of red pigments

Abstract: A higher producer of ascospores and pigments, Monascus strain TTWMB 6042, was used to study regulation of pigment production by nutrients. An initial medium containing 4% glucose, 0.3% NHaNO3 (75 mM nitrogen) and inorganic salts was used. We found that the formation of red pigments in this strain, measured by optical density at 500 nm (OD5oo) was strongly stimulated by monosodium glutamate (MSG) as the sole nitrogen source. The choice of carbon source and an initial pH of pH 5.5 were also important. High conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(63 citation statements)
references
References 8 publications
3
58
0
Order By: Relevance
“…Chen and Johns (1993) in a study of a Monascus purpureus culture demonstrated the presence of yellow pigments (ankaflavin) at a low pH (4.0) and red pigments (monascorubramine) at higher pH (6.0), contrary to the results obtained in our research. Other authors (Lin and Demain, 1991;Orozco and Kilikian, 2008) found a positive effect on cellular growth due to the pH of the culture medium, favoring the production of red pigments intracellularly and extracellularly (secondary metabolites) at a pH of 5.5, as shown in our study. These results suggest that pH can affect the activities of enzymes involved in the biosynthesis of pigments, but the effect depends on the particular microorganism utilized.…”
Section: Resultssupporting
confidence: 87%
“…Chen and Johns (1993) in a study of a Monascus purpureus culture demonstrated the presence of yellow pigments (ankaflavin) at a low pH (4.0) and red pigments (monascorubramine) at higher pH (6.0), contrary to the results obtained in our research. Other authors (Lin and Demain, 1991;Orozco and Kilikian, 2008) found a positive effect on cellular growth due to the pH of the culture medium, favoring the production of red pigments intracellularly and extracellularly (secondary metabolites) at a pH of 5.5, as shown in our study. These results suggest that pH can affect the activities of enzymes involved in the biosynthesis of pigments, but the effect depends on the particular microorganism utilized.…”
Section: Resultssupporting
confidence: 87%
“…In addition, peptone gave better growth and pigment amounts when compared to the sodium nitrate and ammonium chloride [8]. Also, monosodium glutamate was the most favourable nitrogen source for the formation of the red pigments in MOPS-buffered (3-(N-morpholino) propane sulfonic acid) culture [34].…”
Section: Discussionmentioning
confidence: 95%
“…83,84 Nutritional control of the formation of the red pigments has been described in a series of publications by Lin and Demain. [85][86][87][88] C50 carotenoids, such as sarcinaxanthin and its glucosides, are more powerful quenchers of singlet oxygen than β-carotene. They have potential for use in nutriceuticals, pharmaceuticals and derived products such as apocarotenoids or norisoprenoids.…”
Section: Antineoplastic Drugsmentioning
confidence: 99%